Genetic Diversity of Multiple Antibiotic Resistance Streptococcus agalactiae Isolated from Bovine Mastitis and Retail Markets Milk by Enterobacterial Repetitive Intergenic Consensus PCR (ERIC-PCR) - Abd-Elfatah, Alaa; Elkenany, Rasha; Younis , Gamal (Journal of Advanced Veterinary Research, 2023)
Public health is at risk because Streptococcus agalactiae is increasingly linked to incidences of bovine mastitis in Egypt. In this study, enterobacterial repetitive intergenic consensus PCR (ERIC-PCR) were used to explore the genotyping of several antibiotic resistant Streptococcus agalactiae isolated from bovine mastitis and retail milk. Also, antimicrobial resistance genes were detected. Two hundred and sixty-six (46.7%) strains were isolated from samples of milk obtained from cases of bovine mastitis in dairy farms and retail markets representing 34 (5.96%) Streptococcus agalactiae and 232 (40.7%) other Streptococcus species strains based bacterial identification. By using of disc diffusion assays, it was examined the susceptibility of all Streptococcus isolates to twelve antimicrobial agents. The highest prevalence of resistance of Streptococcus species was observed against ampicillin (65.5%), amoxicillin (56%), tetracycline (52.5%), ofloxacin (47.8%), and nitrofurantoin (46.9%). High proportion of the S. agalactiae isolates were resistance to amoxicillin (83%), followed by tetracycline (82.4%), nitrofurantoin (64.7%), azithromycin (61.8%), and ampicillin (50%). Most (88.2%) of S. agalactiae showed multiple antibiotic resistances (MAR) phenotypes with MAR index of 0.1-0.7 and 28 different MAR patterns. The results of genetic antimicrobial resistance of S. agalactiae strains revealed amplification of blaTEM (23%) and blaCTX (26%) genes in β-lactam-resistant strains, erm(B) gene (20%), mef(A) (35%) in macrolides resistant isolates, and tet(M) in (44%) tetracycline resistant strains. Using ERIC-PCR, the present study showed the genetic diversity and heterogeneity among S. agalactiae strains (n=34) that were classified into 19 distinct ERIC-PCR groups (A–S). Between them, ERIC O (20.6%, 7) was the most widespread group. These results indicated that milk samples served as source of MAR S. agalactiae, consequently posing threats to public health, so the improvement of the hygiene regimen on the farms and promotion of the wise use of antimicrobials are necessary. The obtained findings showed that milk samples were a source of MAR S. agalactiae, endangering public health. As a result, it is essential to enhance farm hygiene practices and promote the responsible use of antimicrobials. Additional research on the epidemiology of S. agalactiae is required to add bacterial genetic information in order to help in rational vaccine strategy in the future.